AdJusting Jonah - Havea, Jione (International review of mission, 2013)
In this article, I engage the theme for the WCC Busan assembly – “God of Life, Lead Us to Justice and Peace” – through a reading of the story of Jonah that listens for the currents and vibes in and from Oceania. I circle around the story of Jonah with a double-edging (AdJusting) reading: first, listening for justice (Justing) in the story of Jonah and second, shifting (Adjusting) the way we hear (read, view) Jonah. I hear Jonah's Wrath as a call for justice, with calm and respect of someone who is angry but at peace. Jonah did not agree with G*d from the start, seeing that Nineveh was not as wicked as G*d claimed, and at the end of the story Jonah is silent because he did not want Nineveh's countless cattle (like pigs in my culture) to be destroyed.